Pentingnya Kualitas Pelayanan Dibanding Harga: Kepuasan Konsumen pada Jasa Roasting Kopi di Daerah Pedesaan Indonesia - Setiawan, Riki; Suhendi, Andreas; Ardianto, Victor Marindra; Arpan, Yunada (Lembaga Penelitian, dan Pengabdian Kepada Masyarakat (LPPM) STIE GENTIARAS Bandar Lampung dan berkolaborasi dengan Ikatan Akuntan Indonesia Kompartemen Akuntan Pendidik (IAI KAPd), 2025)
The coffee agro-industry in Indonesia is growing, increasing the demand for quality roasting services. Consequently, service quality and price have become important components in determining customer satisfaction. However, there is no empirical evidence on how these two components influence satisfaction in local coffee roasting MSMEs. The purpose of this study was to evaluate the influence of service quality and price on customer satisfaction with coffee roasting services at “Coffee Srimenganten”, Pulau Panggung. This study used a quantitative approach designed as a survey. Data were collected through a structured questionnaire administered to 72 customers who had used the roasting service at least twice. Validity and reliability tests, as well as classical assumption tests (normality and multicollinearity), were conducted before data analysis using multiple linear regression. T-tests and F-tests were used to test the hypotheses. The results showed that, although price did not partially influence customer satisfaction, service quality had a positive and significant effect on customer satisfaction. However, both significantly influenced customer satisfaction. The results indicate that customers are more sensitive to service quality in coffee roasting services compared to price variations within a reasonable range. Practically, this study shows that coffee roasting MSMEs must prioritize consistent, responsive, and reliable service as the main way to maintain customer satisfaction and loyalty.